Income Tax Preparation System / Ku Seng Lip - Ku, Seng Lip (2001)
Final year thesis is one of major requirements to fulfill Bachelor Degree in Computer Science at University Malaya, We need to develop a system alone or in one group from beginning stage of literature survey until the system was delivered. I had been chosen to develop a system so call income tax preparation system, which require assisting taxpayers to prepare the return forms and furnish estimate of the tax payable for the year of assessment. At the same time calculate tax to be pay to Lembaga Hasil Dalam Negeri Malaysia (LHDN) by monthly payments. The system will be developed for individual taxpayers assist them self-assess their income tax electronically My friend Mr. Lee Hong Yin and I will work together to develop this system. The reason why I choose this topic is because I am interest with the Self-Assessment System that will fully applicable by LHDN to the individual taxpayers or employee in year of 2004. The Self-Assessment System requires taxpayers self-assess the tax to be paid for the current year of assessment. After Self-Assessment System fully applicable to the taxpayers, the Income Tax Preparation System will be very useful for the taxpayers.